2023
DOI: 10.1021/jacs.2c13784
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Dependent Active Sites on Cu/ZnO Clusters for CH3OH Synthesis

Abstract: This study describes an instantaneously gas-induced dynamic transition of an industrial Cu/ZnO/Al 2 O 3 catalyst. Cu/ ZnO clusters become "alive" and lead to a promotion in reaction rate by almost one magnitude, in response to the variation of the reactant components. The promotional changes are functions of either CO 2 -to-CO or H 2 O-to-H 2 ratio which determines the oxygen chemical potential thus drives Cu/ZnO clusters to undergo reconstruction and allows the maximum formation of Cu−Zn 2+ sites for CH 3 OH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 27 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…For the Cu/Al 2 O 3 ‐CO 2 /H 2ZnO ‐100 catalyst, only the Auger peak of Zn 2+ at 498.2 eV exists, while an obvious shoulder feature of Zn 0 at 493.6 eV appears in addition to the Auger peak of Zn 2+ in the Cu/Al 2 O 3 ‐H 2ZnO ‐100 catalyst. Besides, Cu 2p and Cu LMM Auger spectra acquired from quasi in situ X‐ray photoelectron spectroscopy (XPS) experiments of the two catalysts show the identical Cu 2p 3/2 core level peak (932.0 eV) and Cu LMM Auger peak (567.4 eV) of Cu 0 (Figure S1), confirming that Cu NP S exist in the form of a metallic state in these catalysts after the treatment [9] . High‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) and corresponding energy dispersive spectroscopy (EDS) elemental analysis have been utilized to observe distribution of Zn species in the catalysts.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…For the Cu/Al 2 O 3 ‐CO 2 /H 2ZnO ‐100 catalyst, only the Auger peak of Zn 2+ at 498.2 eV exists, while an obvious shoulder feature of Zn 0 at 493.6 eV appears in addition to the Auger peak of Zn 2+ in the Cu/Al 2 O 3 ‐H 2ZnO ‐100 catalyst. Besides, Cu 2p and Cu LMM Auger spectra acquired from quasi in situ X‐ray photoelectron spectroscopy (XPS) experiments of the two catalysts show the identical Cu 2p 3/2 core level peak (932.0 eV) and Cu LMM Auger peak (567.4 eV) of Cu 0 (Figure S1), confirming that Cu NP S exist in the form of a metallic state in these catalysts after the treatment [9] . High‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) and corresponding energy dispersive spectroscopy (EDS) elemental analysis have been utilized to observe distribution of Zn species in the catalysts.…”
Section: Resultsmentioning
confidence: 80%
“…Besides, Cu 2p and Cu LMM Auger spectra acquired from quasi in situ X-ray photoelectron spectroscopy (XPS) experiments of the two catalysts show the identical Cu 2p 3/2 core level peak (932.0 eV) and Cu LMM Auger peak (567.4 eV) of Cu 0 (Figure S1), confirming that Cu NP S exist in the form of a metallic state in these catalysts after the treatment. [9] Highangle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and corresponding energy dispersive spectroscopy (EDS) elemental analysis have been utilized to observe distribution of Zn species in the catalysts. The Cu/Al 2 O 3 catalyst (Figure S2) shows clean Cu particle surface.…”
Section: Resultsmentioning
confidence: 99%
“…Cu-based catalysts show broad applicability in the chemical industry for the hydrogenation of carbon–oxygen bonds in aldehydes, , CO/CO 2 , , acids, and esters, due to its moderate ability toward hydrogen activation and inactive toward the C–C cleavage. , To reveal the active sites of Cu-based catalysts is a hot research topic in scientific and practical research. The strong metal and support interaction stabilizes Cu species and introduces interfacial sites, including Cu 0 –Cu + and O V -included Cu–O x –support (0 < x < 2, O V represents oxygen vacancies on reducible oxides). The synergy between Cu 0 and Cu + has been proved to enhance reaction rates, with Cu 0 facilitating H 2 dissociation and Cu + targeting carbonyl groups. Despite being cited and discussed by numerous researchers, this conclusion lacks kinetic evidence to verify the respective roles of Cu + and Cu 0 . Moreover, the reason why a balanced Cu + /Cu 0 ratio improves the activity of Cu-based catalysts remains a topic of debate. , Moreover, the influence of the Cu valence state on product distributions is vital but has received limited attention to date. , Another scientific issue is discussed about the interface between Cu and support, which has been verified to heterolytically dissociate H 2 and stabilize transition states, thereby promoting the hydrogenation of dimethyl oxalate (DMO) on Cu/SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…2,9–11 Many studies have shown that copper catalyst with a ZnO-based support is active for the methanol synthesis process in CO 2 hydrogenation. 10,12–15 For instance, Kattel et al reported that the ZnO–Cu interface was the active site for methanol synthesis from CO 2 hydrogenation via a formate intermediate. 12 Behrens et al highlighted that the presence of Cu steps decorated with Zn atoms resulted from the strong metal–support interaction in the industrial Cu/ZnO/Al 2 O 3 catalyst significantly boosted the adsorption of the intermediates and thus promoted methanol formation.…”
Section: Introductionmentioning
confidence: 99%